2015
DOI: 10.1021/la5041213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Texture on Freezing in Nanopores: Surface-Induced versus Homogeneous Crystallization

Abstract: Freezing of argon in ordered and disordered carbon pores of a similar diameter D ∼ 2.4 nm is investigated using extensive molecular simulations with large system sizes up to 10(4) atoms. While crystallization in the atomistically smooth pore consists in a surface-induced phase transition occurring at a temperature larger than the bulk, crystallization in the disordered pores, which is only partial as it is spatially restricted to the pore center, occurs through homogeneous crystallization. These results shed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(133 reference statements)
1
5
0
Order By: Relevance
“…Surface premelting is also observed in nanoporous materials, and melting temperature was related to the size of pores. A roughly proportional function is shown between the melting temperature and reciprocal of averaged pore-size, as predicted by Gibbs-Thomson equation [29], which is consistent with the experimental reports using nuclear magnetic reso-nance (NMR) [30] and X-ray diffraction techniques [31] and the atomistic simulation studies [32][33][34][35]. These studies enriched our knowledge of the melting in nanoporous materials.…”
Section: Introductionsupporting
confidence: 86%
“…Surface premelting is also observed in nanoporous materials, and melting temperature was related to the size of pores. A roughly proportional function is shown between the melting temperature and reciprocal of averaged pore-size, as predicted by Gibbs-Thomson equation [29], which is consistent with the experimental reports using nuclear magnetic reso-nance (NMR) [30] and X-ray diffraction techniques [31] and the atomistic simulation studies [32][33][34][35]. These studies enriched our knowledge of the melting in nanoporous materials.…”
Section: Introductionsupporting
confidence: 86%
“…Finally, because the distinct layers are still amorphous, even after capillary condensation raises the density to near-liquid conditions, further densification cannot proceed without a structural reorganization that increases the free volume of each layer. The third open question is the role of surface roughness in the real materials. , The SANS experiments indicated significant roughness, while our model silica is perfectly smooth, which could either promote or retard 2D ordering of the adsorbed methane depending on the exact nature of that roughness.…”
Section: Discussionmentioning
confidence: 85%
“…The third open question is the role of surface roughness in the real materials. 74,75 The SANS experiments indicated significant roughness, 49 while our model silica is perfectly smooth, which could either promote or retard 2D ordering of the adsorbed methane depending on the exact nature of that roughness.…”
Section: ■ Summary and Conclusionmentioning
confidence: 83%
“…Obviously, it modifies the molecular arrangement of the confined oxygen in comparison to bulk and as a consequence the elastic behavior is altered. Simulations have shown that the structure of the pore surface and hence its interaction with the adsorbate influence also the phase behavior of adsorbate (see ref for adsorbed argon).…”
Section: Measurements and Analysismentioning
confidence: 99%